Data for: Gut microbiota markers in early childhood are linked to farm living, pets in household and allergy - Adlerberth, Ingegerd; Wold, Agnes; Hesselmar, Bill (University of Gothenburg, 2024)
These data underly a study which described longitudinal gut microbiota development during early childhood, and investigated associations with early life exposures and allergy outcomes.

The dataset includes variables on:

Host factors and early life exposures: sex, parental allergy, farm residence, pet ownership, and breastfeeding

Gut microbiota development: presence and population counts of selected bacterial groups at 9 timepoints between 3 days and 18 months of age. These data were obtained using quantitative bacterial culture of fecal samples, targeting key facultative and anaerobic bacteria of the infant gut (exception: samples obtained at 3 days of age were not cultured quantitatively and targeted facultative bacteria only).

Allergy at 3 and 8 years of age: clinical diagnosis of allergy (eczema, food allergy, allergic rhinoconjunctivitis or asthma)

Dessa data ligger till grund för en studie som beskriver tarmflorans utveckling över tid under tidig barndom, och undersöker tarmflorans sammansättning i relation till vissa tidiga exponeringar och till senare allergiutveckling.

Datasetet inkluderar följande variabler:

Värdfaktorer och tidiga exponeringar: kön, hereditet för allergi, uppväxt på bondgård, husdjur och amning.

Tarmfloran: förekomst och populationstal för ett antal olika bakteriegrupper vid 9 provtagningstillfällen mellan 3 dagar och 18 månaders ålder. Bakteriadata är baserade på kvantitativ odling av faecesprover med identifiering av fakultativa och anaeroba bakterier som är vanligt förekommande i den tidiga tarmfloran (undantag prover tagna vid 3 dagars ålder som inte odlades kvantitativt och enbart fakultativa bakterier identifierades i dessa).

Allergi vid 3 och 8 års ålder: klinisk allergidiagnos (eksem, födoämnesallergi, allergisk rinokonjunktivit eller astma)
Data för: Gut microbiota markers in early childhood are linked to farm living, pets in household and allergy
Keywords: Child; Barn; Pets; Sällskapsdjur; Hypersensitivity; Överkänslighet; Breast Feeding; Amning; Bacteria; Bakterier; Infant; Spädbarn; Intestines; Tarmar; Colony Count, Microbial; Mikrobiell koloniräkning; Gastrointestinal Microbiome; Tarmflora; Birth Cohort; Födelsekohort; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap